Carotenoids Inhibit Fructose-Induced Inflammatory Response in Human Endothelial Cells and Monocytes - Ping Lin; Qian Ren; Qin Wang; Jiali Wu (Mediators of Inflammation)
Objective. This research is aimed at determining the vascular health characteristics of carotenoids by evaluating their effect on excessive inflammatory response in endothelial and monocyte cells, the main factors of atherosclerosis. Methods. Human umbilical vein endothelial cells (HUVECs) or U937 monocytes were treated with escalating concentrations (0.1, 0.5, and 1 μM) of five most common carotenoids in human plasma, i.e., α-carotene, β-carotene, β-cryptoxanthin, lutein, and lycopene prior to stimulation with 2 mM fructose. We examined the monocyte adhesion to endothelial cells (ECs) and relevant endothelial adhesion molecules. Chemokine and proinflammatory cytokine production as well as intracellular oxidative stress were also assessed in fructose-stimulated ECs and monocytes. Results. Carotenoids repressed monocyte adhesion to fructose-stimulated ECs dose dependently via decreasing primarily the expression of endothelial VCAM-1. In ECs and monocytes, three carotenoids, i.e., β-cryptoxanthin, lutein, and lycopene, suppressed the fructose-induced expression of chemokines MCP-1, M-CSF, and CXCL-10 and inflammatory cytokines TNF-α and IL-1β, with CXCL-10 being the most repressed inflammatory mediator. β-Cryptoxanthin, lutein, and lycopene dramatically downregulated the fructose-induced CXCL-10 expression in vascular cells. The reduction in the inflammatory response was associated with a slight but significant decrease of intracellular oxidative stress. Conclusions. Our results show that carotenoids have a variety of anti-inflammatory and antiatherosclerosis activities, which can help prevent or reduce fructose-induced inflammatory vascular diseases.